A study of relationship between return on equity and foreign ownership of selected industrial countries in Kuala Lumpur Stock Exchange - Arifin, Mohd Bukhari (1997)
The main questions for this study are how much foreigners owned the company, is there any relationship exist between foreign ownership and return on equity, how the return on equity affect their ownership and how could we maintain their participation in the company. Limitation on 24 companies will represent 30% of total industrial counters in the Kuala Lumpur Stock Exchange. Absence of proper recorded data for share distribution limits my research for seven years starting from 1990 to 1996. This study also differentiate between the concept of ownership and control. However, the primary concern of this study is ownership of company's stock in industrial sector.